Peri- and postoperative complications in Le Fort I osteotomies. Issue 9 (September 2021) - Kotaniemi, Karoliina V.M.; Suojanen, Juho; Palotie, Tuula
Abstract: This retrospective study was performed to report the peri- and postoperative complications encountered by patients who underwent Le Fort I osteotomy, as well as predictor variables affecting the risk of complications. Patients who underwent only Le Fort I osteotomy were included in the study. Information on peri- and postoperative complications were collected from the patient data records. The effects of certain predictor variables on complication rates were also studied. Twenty-four per cent of the patients suffered from complications, six (6.1%) of whom were reoperated. Most of the complications were minor and transient. Compared with one-piece osteotomy, segmental osteotomy was a significant risk factor predisposing patients to postoperative complications ( p  = 0.04619). Additionally, the use of patient-specific implants seemed to increase the risk of both perioperative and postoperative complications ( p  = 0.0248). Currently, the conventional plate fixation method is the primary method in Le Fort I osteotomies. Careful patient selection, surgical planning, and selection of surgical technique seem to be the most important factors in reducing the complication risk. Special attention should be paid with segmental osteotomy surgery.